Method for preparing garnet-type inorganic material
By adding zirconium salt, lanthanum salt and element A salt or oxide of element A dropwise in the aqueous solution, and contacting the lithium salt after calcining at high temperature, LLZ garnet-type material with fine particles is prepared, which solves the problem of difficulty in preparing fine particles and lithium volatility in the prior art, and achieves efficient process flow and material properties.
Patent Information
- Application Number
- CN202080055129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2020-07-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-07-29
AI Technical Summary
It is difficult to prepare fine particles of LLZ garnet-type materials in the prior art, and the high-temperature calcination process is prone to grain growth and lithium volatility, affecting the economics and environmental friendliness of the process.
Fine particles of LLZ garnet-type material are prepared by adding dropwise zirconium salt, lanthanum salt and element A salt or oxide in aqueous solution, then contacting with alkaline compounds, and then calcining at high temperatures, and finally calcining at a specific temperature.
The preparation of fine and easily dispersed LLZ garnet-type material particles is achieved, which improves the contact efficiency with the electrode layer or the separator, reduces the volatility of lithium, and improves the economicality and environmental friendliness of the process.
Smart Images

Figure BDA0003493765900000231
Abstract
Description
[0001] This application claims priority to European patent application EP 19315084.4 filed on August 6, 2019, the contents of which are fully incorporated by reference into this application for all purposes. In the event of any inconsistency between this application and the EP application that would affect the clarity of terminology or expression, reference should be made only to this application.
[0002] The present invention relates to a method for preparing a garnet-type inorganic material and also to the garnet-type inorganic material itself. Technical Field
[0003] In recent years, garnet-type inorganic materials have attracted attention as potential materials that can contribute to the development of all-solid-state lithium batteries. In fact, J.Am.Ceram.Soc. [Journal of the American Ceramic Society], 2003, Vol. 86, pp. 437-440 reported a garnet-type inorganic material having the formula Li5La3M2O 12 Garnet-type materials (wherein M is Nb or Ta) are solid electrolyte materials with remarkable lithium ion conductivity.
[0004] Angew.Chem.Int.Ed., 2007, Vol. 46, pp. 7778-7781 reported another Li7La3Zr2O 12 (hereinafter referred to as "LLZ") is a garnet-type material based on Li, Al and Zr, which is prepared by synthesizing Li5La3M2O 12 The solid electrolyte material obtained by replacing Nb or Ta with Zr also has significant lithium ion conductivity.
[0005] Garnets have long been known and originally corresponded to orthosilicates having the formula A3B2(SiO4)3, wherein A and B refer to an octacoordinated cation site and a hexacoordinated cation site, respectively. Lithium-containing garnets are obtained by replacing silicon with lithium to provide the general composition A3B2(LiO4)3. Since the garnet structure is able to accept a wide variety of atoms of different sizes and charges, a variety of different lithium oxide garnets have been prepared in which the lithium is in alternative sites. In fact, the lithium content can be increased by replacing A and / or B with cations having a higher or lower oxidation state, thereby obtaining lithium-containing garnets, such as the promising Li7La3Zr2O having the formula 12 (LLZ) solid electrolyte material.
[0006] Compared with the "ideal" garnet-type structure, the two materials Li5La3M2O 12 and Li7La3Zr2O 12Contains excess Li. Having this specific crystal structure is believed to be one of the reasons why these compounds exhibit high lithium ion conductivity in the solid state. In particular, it was found that LLZ containing Al as a dopant exhibited a high conductivity of up to 10 -4 S / cm high lithium ion conductivity.
[0007] Technical issues
[0008] The method for preparing LLZ garnet-type materials in the form of fine particles is desirable for preparing all-solid lithium secondary batteries. In fact, these particles are used for the preparation of electrode layers or separator layers. Seeking fine particles is to enhance the contact with other components of the electrode layer or separator. In addition, fine particles also enable the preparation of thin electrode layers and thin separators, which are generally conducive to higher energy density.
[0009] The conventional method for preparing LLZ garnet-type materials using a solid-state reaction process includes a calcination step at a high temperature of 1,000° C. to 1,200° C. (see, for example, Angew. Chem. Int. Ed. [German Applied Chemistry], 2007, Vol. 46, pp. 7778 to 7781, which discloses a calcination step at a temperature > 1000° C.). When calcination is performed at such a high temperature, grain growth is easily promoted, which makes it difficult to directly obtain fine particles. In addition, calcination at 1,000° C. or higher is usually accompanied by the volatilization of a large amount of lithium, which is a problem for both the economy and the environment of the process.
[0010] It is also desirable to have particles that can be easily dispersed in solvents used to prepare electrodes and separators.
[0011] Therefore, there is a need for a process for preparing LLZ garnet-type materials in the form of fine and easily dispersible particles. Background Art
[0012] JP 2012-224520 discloses a method involving the preparation of a LLZ garnet-type material by co-precipitation using a solution containing all elements including lithium.
[0013] US 2018 / 0248223 and US 2019 / 0051934 disclose a method for preparing LLZ garnet-type materials by co-precipitation with aminopyralid.
[0014] JP 2012 / 224520, JP 2013 / 256435, JP 2018 / 065704, US 2018 / 175446 and US 2019 / 0036159 do not disclose the method of the present invention, nor the claimed inorganic material M. Summary of the invention
[0015] The present invention relates to an inorganic material M as claimed in any one of claims 1 to 22 or claim 30. The present invention also relates to a method for preparing an inorganic material M as claimed in any one of claims 23 to 29. The present invention also relates to a composition (C), an electrode (E) or a separator (SP) as claimed in claims 31, 32 and 33, respectively. The present invention also relates to the use of the inorganic material M as claimed in claim 34, and to a battery comprising the inorganic material M as claimed in claim 35.
[0016] These objectives will now be described further.
[0017] The present invention
[0018] The present invention relates to a method for preparing an inorganic material M, the method comprising the following steps:
[0019] (1) contacting an aqueous solution S containing (i) a zirconium salt, (ii) a lanthanum salt and (iii) a salt of element A or a precursor of an oxide of element A with an aqueous solution of a basic compound, resulting in a precipitate suspended in a reaction medium;
[0020] (2) stirring the reaction medium obtained at the end of step (1) for at least 30 minutes;
[0021] (3) contacting the precipitate obtained at the end of step (2) with an additive selected from the group consisting of anionic surfactants, nonionic surfactants, polyethylene glycol, carboxylic acids and their salts, and a surfactant of the carboxymethylated fatty alcohol ethoxylate type;
[0022] (4) calcining the precipitate recovered at the end of the previous step in air at a temperature of at least 400° C.;
[0023] (5) contacting the product obtained at the end of step (4) with a lithium salt;
[0024] (6) calcining the product obtained at the end of step (5) in air at a temperature between 700° C. and 1100° C.;
[0025] The inorganic material M is an oxide containing, as constituent elements, elements Li, La, Zr, and at least one element A selected from the group consisting of Al, Ga, Nb, Fe, W, Ta, or a mixture thereof.
[0026] The inorganic material M may be described as exhibiting the structure of a garnet. In the context of the present invention, the oxide may thus be referred to as a garnet or a garnet-type oxide.
[0027] In step (1), an aqueous solution S containing (i) a zirconium salt, (ii) lanthanum nitrate and (iii) a salt of element A or a precursor of an oxide of element A is brought into contact with a solution of a basic compound.
[0028] The zirconium salt is conveniently chosen between zirconium nitrate and zirconium chloride. The zirconium salt may be, for example, zirconium nitrate or zirconium oxynitrate. The zirconium salt may be a crystalline zirconyl nitrate. The zirconium salt may also be a zirconium nitrate solution obtained by dissolving zirconium carbonate or zirconium hydroxide with nitric acid. This acid etching may preferably be carried out at a NO3 concentration between 1.7 and 2.3. - In the case of zirconium carbonate, this ratio may be between 1.7 and 2.0.
[0029] The lanthanum salt may be lanthanum nitrate.
[0030] The source of the oxide of element A may be a salt of element A or a precursor of the oxide of element A. The source of element A may be a salt of element A, such as iron nitrate (e.g., Fe(NO3)3), aluminum nitrate Al(NO3)3, or gallium nitrate Ga(NO3)3. The source of element A may be a precursor of the oxide of element A, such as a coordination complex of element A, such as niobium oxalate. The precursor of the oxide of element A may be an oxalate of element A. For example, the precursor of niobium oxide may be ammonium niobium oxalate.
[0031] As the basic compound, a hydroxide type or carbonate type compound can be mentioned. The basic compound can be an alkali metal hydroxide or an alkaline earth metal hydroxide. The basic compound can also be ammonia, a secondary amine, a tertiary amine or a quaternary amine. Ammonia is preferred because ammonia provides a strongly alkaline aqueous solution and because the released ammonium salt can be efficiently washed off.
[0032] Step (1) can be carried out by introducing the aqueous solution S into the aqueous solution of the basic compound. Under laboratory scale, the aqueous solution S can be introduced into the aqueous solution of the basic compound, for example, dropwise. The duration of the introduction can be between 30 and 120 minutes, more particularly between 30min and 100min.
[0033] Step (1) may conveniently be carried out at a temperature between 5°C and 40°C, more particularly between 10°C and 30°C, more particularly between 15°C and 25°C.
[0034] The amount of basic compound used for the precipitation of step (1) is such that the pH of the mixture obtained at the end of step (1) is at least 7.0, more particularly at least 9.0. The amount of basic compound used is such that the molar ratio r is higher than 1.0, more particularly greater than or equal to 1.2 (≥1.2), more particularly greater than or equal to 1.4 (≥1.4), where r=amount of basic compound / total amount of elements Zr, La, A in solution S.
[0035] At the end of step (1), the reaction medium comprises the precipitate dispersed in an aqueous medium.
[0036] In step (2), the reaction medium obtained at the end of step (1) is stirred for at least 30 min. According to an embodiment, the reaction medium is stirred for at least 30 minutes, and the temperature of the reaction medium is between 50 ° C and 200 ° C, more particularly between 80 ° C and 150 ° C. The duration of step (2) can be between 30 minutes and 10 hours, more particularly between 30 minutes and 5 hours, even more particularly between 1 hour and 5 hours. The reaction medium comprises a precipitate dispersed in an aqueous medium. Step (2) is conveniently carried out in a closed container, such as a stirred tank reactor.
[0037] In step (3), the precipitate obtained at the end of step (2) is contacted with an additive selected from the group consisting of anionic surfactants, nonionic surfactants, polyethylene glycol, carboxylic acids and their salts, and a surfactant of the carboxymethylated fatty alcohol ethoxylate type. Step (3) can be carried out by adding the additive to a dispersion of the precipitate obtained at the end of step (2) in an aqueous medium. It has been found that the additive contributes to obtaining an inorganic material M having a pure cubic phase (see Comparative Example 2).
[0038] As surfactants of the anionic type, mention may be made of ethoxycarboxylates, ethoxylated fatty acids, sarcosinates, phosphates, sulfates such as alcohol sulfates, alcohol ether sulfates and sulfated alkanolamide ethoxylates, and sulfonates such as sulfosuccinates, and alkylbenzene or alkylnaphthalenesulfonates. As nonionic surfactants, mention may be made of acetylenic surfactants, alcohol ethoxylates, alkanolamides, amine oxides, ethoxylated alkanolamides, long-chain ethoxylated amines, ethylene oxide / propylene oxide copolymers, sorbitan derivatives, ethylene glycol, propylene glycol, glycerol, polyglycerol esters and ethoxylated derivatives thereof, alkylamines, alkylimidazolines, ethoxylated oils and alkylphenol ethoxylates. Mention may be made in particular of the surfactants sold under the trademark ETHOXYL. and Products for sale.
[0039] Regarding carboxylic acids, in particular aliphatic monocarboxylic acids or dicarboxylic acids can be used, and among these, more particularly saturated acids. Fatty acids and more particularly saturated fatty acids can also be used. Therefore, formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid and palmitic acid can be mentioned in particular. As dicarboxylic acids, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid can be mentioned. Salts of carboxylic acids can also be used, particularly ammonium. The additive can more particularly be lauric acid or ammonium laurate.
[0040] Finally, it is possible to use surfactants chosen from those of the carboxymethylated fatty alcohol ethoxylate type. The expression "product of the carboxymethylated fatty alcohol ethoxylate type" is intended to mean a product consisting of ethoxylated or propoxylated fatty alcohols comprising a -CH2-COOH group at the end of the chain. These products may correspond to the following formula:
[0041] R1-O-(CR2R3-CR4R5-O) n -CH2-COOH
[0042] wherein R1 represents a saturated or unsaturated carbon-based chain, the length of which is generally up to 22 carbon atoms, preferably at least 12 carbon atoms; R2, R3, R4 and R5 may be identical and may represent hydrogen, or R2 may represent an alkyl group such as a CH3 group and R3, R4 and R5 represent hydrogen; n is a non-zero integer which may be up to 50 and more particularly between 5 and 15 (these values are included). It should be noted that the surfactant may consist of a mixture of products having the above formula (wherein R1 may be saturated or unsaturated, respectively) or alternatively a mixture of products containing both -CH2-CH2-O- and -C(CH3)=CH2-O- groups.
[0043] The additives may be added as such, or as a suspension or solution in a liquid medium.
[0044] The amount of additive added, expressed as the ratio of the weight of the additive to the weight of the inorganic material M (weight of the additive / weight of the inorganic material M x 100), is generally between 5% and 100%, more particularly between 15% and 60%, preferably between 30% and 50%. The amount may be as in Example 1 (additive / inorganic material M=40%).
[0045] The method of the present invention may further comprise a step (3a) after step (3), wherein the solid obtained at the end of step (3) is washed with water. An alkaline aqueous solution (e.g. ammonia gum) may be conveniently used in step (3a). The pH of the alkaline aqueous solution may be at least 8.0.
[0046] In step (4), the precipitate obtained at the end of the previous step (i.e., step (3) or step (3a)) is calcined in air at a temperature of at least 400°C. The temperature should be high enough to at least partially induce the decomposition of the additive and the release of the nitrate. The product obtained at the end of step (4) preferably contains a residual carbon content of less than 2.0 wt%. In practice, the calcination temperature can be between 400°C and 800°C, more particularly between 400°C and 600°C. Higher temperatures are likely to cause some sintering, which tends to reduce the specific surface area of the product obtained. The duration of calcination depends on the calcination temperature. The duration of calcination is generally between 30 minutes and 10 hours, more particularly between 1 hour and 5 hours.
[0047] In step (5), the product obtained at the end of the calcination step (4) is contacted with a lithium salt. A convenient way to carry out step (5) comprises impregnating the product obtained at the end of the calcination step (4) with an aqueous solution of a lithium salt. More particularly, the aqueous solution of a lithium salt can be added dropwise on the solid under stirring. The lithium salt can be, for example, lithium chloride, lithium carbonate, lithium bicarbonate, lithium nitrate or lithium sulfate. The lithium salt can also be selected from lithium carboxylates, such as lithium acetate, lithium citrate or lithium oxalate. Another convenient way to carry out step (5) comprises mixing the product obtained at the end of the calcination step (4) and a lithium salt, both of which are in powder form.
[0048] The amount of lithium added should preferably be slightly greater than the stoichiometric amount to account for some loss of lithium during the calcination step (6). Thus, the molar ratio amount of lithium added / stoichiometric amount of lithium may be between 1.00 and 1.20, more particularly between 1.05 and 1.15.
[0049] In step (6), the product obtained at the end of step (5) is calcined in air at a temperature between 700° C. and 1100° C. The calcined product contains all the elements of the inorganic material M. The duration of calcination may be between 2 and 15 hours, more particularly between 4 and 10 hours.
[0050] In a particular embodiment of step (6), the product obtained at the end of step (5) is first calcined in air at a temperature between 700° C. and 900° C., and then calcined in air at a temperature between 900° C. and 1100° C. In this two-step calcination, the duration of each calcination step may be between 4 and 8 hours. In another particular embodiment of step (6), the product obtained at the end of step (5) is calcined in air at a temperature between 750° C. and 850° C. for a calcination duration between 4 and 8 hours.
[0051] The calcination step (6) is conveniently carried out in a crucible. When the crucible is made of alumina, some aluminum atoms may migrate into the inorganic material M. This enables the preparation of an inorganic material M containing a combination of Al and at least another element A selected from the group consisting of Ga, Nb, Fe, W, and Ta.
[0052] The inorganic material obtained at the end of step (6) is recovered.
[0053] About Inorganic Materials
[0054] The inorganic material M contains the oxide as disclosed above or consists essentially of the oxide as disclosed above. The inorganic material M contains a garnet oxide or garnet-type oxide that exhibits a cubic structure and contains the elements Li, La, Zr, and at least one element A selected from the group consisting of Al, Ga, Nb, Fe, W, Ta, or a mixture thereof as constituent elements, or consists essentially of the garnet oxide or garnet-type oxide.
[0055] The garnet oxide or garnet-type oxide can be described by formula (I):
[0056] [Li x1 La3Zr z A w O 12 (I)
[0057] Wherein:
[0058] ■ x1, z, and w are positive real numbers;
[0059] ■ 1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00;
[0060] ■ 0 < w ≤ 0.80; preferably 0 < w ≤ 0.60; more preferably 0 < w ≤ 0.30; even more preferably 0 < w ≤ 0.25;
[0061] ■ x1 is determined by the electrical neutrality of the oxide.
[0062] A represents at least one element selected from the group consisting of Al, Ga, Nb, Fe, W, Ta, or a mixture thereof, more particularly at least one element selected from the group consisting of Al, Ga, Nb, or a mixture thereof. A can also be selected from the group consisting of W, Ta, Ga, Nb, or a mixture thereof. As a specific embodiment, the inorganic material M contains a combination of Al and another element A selected from the group consisting of Ga, Nb, Fe, W, and Ta.
[0063] z can be in one of the following ranges: 1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00. More particularly, 1.90 ≤ z ≤ 2.10. Even more particularly, z ≤ 2.00.
[0064] w can be in one of the following ranges: 0 < w ≤ 0.80; preferably 0 < w ≤ 0.60; more preferably 0 < w ≤ 0.30; even more preferably 0 < w ≤ 0.25. More particularly, w ≥ 0.05.
[0065] x1 is derived from the electrical neutrality of the oxide. For this purpose, the proportions of the constituent elements of the oxide other than lithium and the oxidation degrees of said elements are considered. In addition, the following oxidation degrees are used: Li +I; Zr +IV; Hf +IV; La +III; Al +III; Ga +III; Nb +V; Fe +III, W +VI; Ta +V. By way of example, for the oxide of Example 1, z = 1.99; w = 0.22, such that x1 = 6.38 (x1 = 24 - 3x3 - 4x1.99 - 3x0.22).
[0066] The inorganic material M and the oxide exhibit a cubic structure. The cubic structure can be determined by XRD. The cubic structure is generally described by the Ia-3d space group and may be described by the I-4 3d space group, especially when A = Ga, Fe or Al+Ga.
[0067] The crystal structure of the oxide is generally composed of a framework of octahedrally coordinated LaO8 dodecahedra and octahedrally coordinated ZrO6 octahedra. More particularly, it can be composed of a framework of octahedrally coordinated LaO8 dodecahedra (24c) and octahedrally coordinated ZrO6 octahedra (16a).
[0068] The relative composition of the cations in the inorganic material M corresponds to the following formula
[0069] Li x La3Zr z A w (II)
[0070] where:
[0071] ■ A is as disclosed above;
[0072] ■ w, x and z are positive real numbers;
[0073] ■ z and w are as disclosed above;
[0074] ■ 4.00 ≤ x ≤ 10.5; preferably 5.10 ≤ x ≤ 9.1; more preferably 6.20 ≤ x ≤ 7.7. More preferably, the relative composition of the cations can be as follows:
[0075] ■A is selected from the group consisting of Nb, Ta, or a combination thereof;
[0076] ■1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00;
[0077] ■0.10 < w ≤ 0.80; preferably 0.20 < w ≤ 0.80; more preferably 0.20 < w ≤ 0.50;
[0078] ■6.20 ≤ x ≤ 10.35; preferably 6.20 ≤ x ≤ 8.84; more preferably 6.50 ≤ x ≤ 7.48. More preferably, the relative composition of the cations can be as follows:
[0079] ■A is W;
[0080] ■1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00;
[0081] ■0.10 < w ≤ 0.80; preferably 0.20 < w ≤ 0.80; more preferably 0.20 < w ≤ 0.50;
[0082] ■5.40 ≤ x ≤ 10.20; preferably 5.40 ≤ x ≤ 8.58; more preferably 6 ≤ x ≤ 7.26. More particularly, the relative composition of the cations can also be as follows:
[0083] ■A is selected from the group consisting of Al, Ga, Fe, or a combination thereof;
[0084] ■1.90 < z ≤ 2.10; preferably 1.95 ≤ z ≤ 2.05; preferably 1.95 ≤ z ≤ 2.00;
[0085] ■0.10 < w ≤ 0.80; preferably 0.20 < w ≤ 0.60; more preferably 0.10 < w ≤ 0.25;
[0086] ■4.60 ≤ x ≤ 10.05; preferably 5.20 ≤ x ≤ 8.32; more preferably 6.25 ≤ x ≤ 7.37. According to the examples, the relative composition of the cations in the inorganic material M can correspond to the following formula
[0087] Li x La3Zr z A1 w1 A2 w2 (IIa)
[0088] Wherein:
[0089] ■A1 is selected from the group consisting of Al, Ga, Fe, or a combination thereof;
[0090] ■ A2 is selected from the group consisting of Nb, Ta, or a combination thereof;
[0091] ■ w1, w2, x, and z are positive real numbers;
[0092] ■ 1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00;
[0093] ■ 0 < w1 ≤ 0.20;
[0094] ■ 0.10 < w2 ≤ 0.80; preferably 0.20 < w2 ≤ 0.80; more preferably 0.20 < w2 ≤ 0.50;
[0095] ■ w1 and w2 are such that w = w1 + w2 and w ≤ 0.80;
[0096] ■ 5.60 ≤ x ≤ 10.35; preferably 5.60 ≤ x ≤ 8.84; more preferably 5.90 ≤ x ≤ 7.48.
[0097] More particularly, according to formula (IIa), A1 = Al. More particularly, according to formula (IIa), A2 = Nb.
[0098] According to the examples, the relative composition of the cations in the inorganic material M can also correspond to the following formula:
[0099] Li x La3Zr z A1 w1 A2 w2 (IIb)
[0100] Where:
[0101] ■ A1 is selected from the group consisting of Al, Ga, Fe, or a combination thereof;
[0102] ■ A2 is W;
[0103] ■ w1, w2, x, and z are positive real numbers;
[0104] ■ 1.20 < z ≤ 2.10; preferably 1.20 < z ≤ 2.05; preferably 1.50 ≤ z ≤ 2.00;
[0105] ■ 0 < w1 ≤ 0.20;
[0106] ■ 0.10 < w2 ≤ 0.80; preferably 0.20 < w2 ≤ 0.80; more preferably 0.20 < w2 ≤ 0.50;
[0107] ■ w1 and w2 are such that w = w1 + w2 and w ≤ 0.80;
[0108] ■4.80≤x≤10.20; preferably 4.80≤x≤8.58; more preferably 5.40≤x≤7.26.
[0109] More particularly, according to formula (IIb), A1 = Al.
[0110] The composition of the inorganic material M and therefore x, z, w, w1 and w2 can be determined by chemical analysis using analytical techniques well known to the skilled person. A convenient method for determining the composition of the inorganic material M and therefore x, z, w, w1 and w2 comprises preparing an aqueous solution obtained by chemical etching of the inorganic material M and determining the content of the elements in the aqueous solution by said analytical techniques. A convenient analytical method is ICP, more particularly ICP-MS (Inductively Coupled Plasma - Mass Spectrometry) or ICP-AES (Inductively Coupled Plasma - Atomic Emission Spectrometry).
[0111] It must be noted that in the context of the present invention, x ≥ x1. This is explained by the fact that elemental lithium is usually added in excess in step (5) of the process to allow for some potential losses under the high temperature calcination of step (6). As an example of this difference, the relative composition of the cations of the inorganic material M of Example 1 corresponds to Li 6.44 LqCy 1.99 Al 0.22 , where x = 6.44, and the composition of the oxide is Li 6.38 LqCy 1.99 Al 0.22 O 12 , where x1=6.38.
[0112] The lithium cations are located within the crystal structure, but may also be located outside the crystal structure. The crystals of the oxide include LiO4 tetrahedra and LiO6 octahedra. More specifically, as summarized in Chem. Lett. [Chemical Journal] 2011, 40, 60-62, the Li + It is generally described as being located in the interstitial site, showing tetrahedral (24d), octahedral (48g), and distorted fourfold (96h) coordination.
[0113] Thus, the inorganic material M may also contain lithium cations outside the crystal structure. - In addition to O2 - The external anion may be, for example, a hydroxide or a carbonate.
[0114] It must be noted that in the ore from which Zr is extracted, Zr is generally associated with Hf. Due to this, the invention also applies to inorganic materials M and oxides in which Zr is partially replaced by Hf. The molar ratio Hf / Zr is generally between 1 / 100 and 5 / 100, more particularly between 1 / 100 and 2 / 100.
[0115] The particles of the inorganic material M are made of finer particles than those prepared by conventional solid-state chemical reactions. Finer particles are more easily dispersed in conventional solvents (e.g., NMP) used to prepare electrodes or separators. They also ensure that the particles are in closer contact with other components of the electrode or separator.
[0116] The particles of the inorganic material M generally exhibit a D50 of between 10.0 μm and 50.0 μm, more particularly between 10.0 μm and 40.0 μm, even more particularly between 10.0 μm and 35.0 μm.
[0117] The particles of the inorganic material M may also exhibit a D90 that is generally less than 150.0 μm. The D90 may be between 20.0 μm and 150.0 μm, more particularly between 20.0 μm and 100.0 μm.
[0118] The particles of inorganic material M may also exhibit a D10 generally greater than and equal to 0.5 μm. The D10 may be between 0.5 μm and 15.0 μm, more particularly between 0.5 μm and 10.0 μm.
[0119] The process of the invention makes it possible to obtain an easily deagglomerated inorganic material M. After treatment under ultrasound, the particles of the inorganic material M generally exhibit a D value lower than and equal to 15.0 μm, more particularly lower than and equal to 10.0 μm, even more particularly lower than and equal to 5.0 μm. US 50. The D US 50 may be between 0.5 μm and 15.0 μm, more particularly between 0.5 μm and 10.0 μm, even more particularly between 1.0 μm and 10.0 μm. Treatment under ultrasound includes inserting an ultrasound probe into a dispersion of 100 mg of the inorganic material M in 160 mL of NMP, and subjecting the dispersion to ultrasound treatment for 22 minutes at a power of 140±10 W. Preferably, the temperature of the dispersion is kept below 45° C., more particularly below 30° C.
[0120] After treatment under ultrasound, the particles of the inorganic material M generally exhibit a D value lower than and equal to 30.0 μm, more particularly lower than and equal to 20.0 μm, even more particularly lower than and equal to 15.0 μm. US 90.
[0121] The particles of inorganic material M thus exhibit large variations in D50 and D90 after treatment under ultrasound. During the ultrasound treatment, D50 and D90 decrease over time. However, it has been observed that these two parameters tend to stabilize before the end of the ultrasound treatment. Thus, D50>D US 50 and D90>D US 90. The changes in D50 and D90 can be checked using the following two ratios:
[0122] R50(%)=(D50-D US 50) / D50 x 100
[0123] R90(%)=(D90-D US 90) / D90 x 100
[0124] R50 may be higher than 50%, more particularly higher than 60%, even more particularly higher than 70% or higher than 80%. R90 may be higher than 50%, more particularly higher than 60%, even more particularly higher than 70% or higher than 80%.
[0125] As shown in the examples, the process of the invention makes it possible to obtain an inorganic material M exhibiting an R50 higher than 70% and / or an R90 higher than 70%. It is also possible to obtain an R50 higher than 80% and / or an R90 higher than 80%.
[0126] D10, D50, D90 have the usual meanings used in the field of particle size distribution, see e.g. https: / / www.horiba.com / fileadmin / uploads / Scientific / Documents / PSA / PSA_Guidebook.pdf Dn thus corresponds to the particle diameter at which n% of the particles have a diameter less than Dn. D50 is thus the median diameter. These parameters are determined from the volume distribution of the diameters of a dispersion of particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameters being obtained using a laser diffractometer. When D50 is measured after a dispersion of the particles in NMP has been treated under ultrasound, it is expressed as D US 50. Similarly, when D90 is measured after a dispersion of particles in NMP is treated under ultrasound, it is expressed as D US 90.
[0127] Laser diffractometers use the technique of laser diffraction to measure the size of particles by measuring the intensity of light scattered when a laser beam passes through a dispersed particle sample. The laser diffractometer can be a Mastersizer 3000 manufactured by Malvern (see https: / / www.malvernpanalytical.com / en / products / product- range / mastersizer-range / mastersizer-3000 ).
[0128] The particles of the inorganic material M ("secondary particles") are aggregates of other finer particles (hereinafter referred to as "primary particles") The primary particles exhibit a d50 between 0.5 μm and 7.0 μm, more particularly between 0.5 μm and 5.0 μm, even more particularly between 0.5 μm and 3.0 μm.
[0129] D50 is obtained by statistical analysis of the (number) distribution of primary particle diameters d, these parameters being determined from at least one photograph obtained by SEM (scanning electron microscope). For D50, d50 corresponds to the median diameter of the distribution. To make sense, preferably a large number of particles are statistically analyzed. This is usually done on more than one photograph of the same sample of particles of the inorganic material M. The number of particles considered for the statistical analysis is preferably greater than 70, more particularly greater than 100, even greater than 200.
[0130] The d50 is measured by observation at a magnification suitable for good observation of the primary and secondary particles. The magnification may be between x1000 and x10000. Of course, the magnification depends on the sample and should be selected on a case-by-case basis. Observation may be performed (i) by image analysis or (ii) by an operator. If the particles are clumping together, observation by an operator is recommended.
[0131] The diameter d of the retained primary particles is the diameter of the circle used to constrain the image of the primary particles as can be seen on the photograph. Only primary particles whose at least half of the circumference is defined are retained. Preferably, the circle must be tangential to the contour of the primary particle up to at least one third of its circumference.
[0132] The process of the invention makes it possible to obtain an inorganic material M exhibiting a pure cubic structure. The expression "pure cubic structure" is understood to mean that the inorganic material M contains a tetragonal phase in a proportion lower than 5.0%. Moreover, it contains a cubic phase in a proportion higher than 95.0%. These proportions can be conveniently obtained by XRD (X-ray diffraction), more particularly using a Rietveld full spectrum fit. It is known that the tetragonal phase belongs to the I 41 / acd space group.
[0133] The method of the present invention also makes it possible to obtain an inorganic material M with a low content of undesirable compounds of the formula La2Zr2O7. In fact, the inorganic material M preferably exhibits an intensity ratio (b / a) of less than 0.05. a and b are the intensities of the peaks visible at 2θ between 16.0° and 17.0° and 2θ between 28.5° and 28.7°, respectively, on the XRD diagram. The higher the intensity ratio (b / a), the more La2Zr2O7 is present as an impurity phase. It is believed that having more La2Zr2O7 as an impurity makes the calcination temperature high. The ratio (b / a) may even be less than 0.02, or less than 0.01. It may be included between 0.001 and 0.05, more particularly between 0.001 and 0.02.
[0134] About Inorganic Materials M Uses
[0135] The inorganic material M disclosed above can be used to prepare a lithium ion battery. The present invention therefore also relates to a lithium ion battery comprising the inorganic material M.
[0136] The inorganic material M disclosed above can be used to prepare an electrode E. The electrode E can be a positive electrode (with E p Indicated by E n express).
[0137] The electrode E of the present invention typically comprises:
[0138] ●Metal substrate;
[0139] at least one layer L directly adhered to the metal substrate, the layer L being made of a composition (C) comprising:
[0140] (i) an inorganic material M as disclosed herein;
[0141] (ii) at least one electroactive compound (EAC);
[0142] (iii) optionally at least one lithium ion conducting material (LiCM) other than the inorganic material M;
[0143] (iv) optionally at least one electrically conductive material (ECM);
[0144] (v) optionally a lithium salt (LIS);
[0145] (vi) optionally at least one polymeric binding material (P).
[0146] The term "electroactive compound" (EAC) is intended to denote a compound that is capable of binding to or inserting into the structure of an electrochemical device and releasing lithium ions during the charging and discharging phases of the electrochemical device. The EAC is thus a compound capable of intercalating and deintercalating lithium ions in the structure of the electroactive device. The properties of the EAC depend on whether the electrode E is the positive electrode or the negative electrode:
[0147] 1) Positive electrode E p
[0148] The EAC can be a complex metal chalcogenide having the formula LiMeQ2, where:
[0149] - Me is at least one metal selected from the group consisting of Co, Ni, Fe, Mn, Cr, Al, and V;
[0150] - Q is a chalcogen element, such as O or S.
[0151] More particularly, the EAC can have the formula LiMeO2. Preferred examples of the EAC include LiCoO2, LiNiO2, LiMnO2, LiNi x Co 1-x O2 (0 < x < 1), LiNi x Co y Mn z O2 (0 < x, y, z < 1 and x + y + z = 1), Li(Ni x Co y Al z )O2 (x + y + z = 1), and spinel-structured LiMn2O4 and Li(Ni 0.5 Mn 1.5 )O4.
[0152] The EAC can also be a lithiated or partially lithiated transition metal oxyanion-based electroactive material having the formula M1M2(JO4) f E 1-f , where:
[0153] - M1 is lithium, which can be partially replaced by another heavy alkali metal that accounts for less than 20% of M1;
[0154] - M2 is a transition metal at an oxidation level of +2, selected from Fe, Mn, Ni, or a mixture thereof, and may be partially replaced by one or more additional metals at an oxidation level between +1 and +5, and these metals account for less than 35% (including 0) of the M2 metal;;
[0155] - JO4 is any oxyanion, where J is P, S, V, Si, Nb, Mo, or a combination thereof;
[0156] - E is a fluoride anion, a hydroxide anion, or a chloride anion;
[0157] -f is the mole fraction of JO4 oxygen anions, typically comprised between 0.75 and 1.
[0158] M1M2(JO4) defined above f E 1-f The electroactive material is preferably phosphate based. It may exhibit an ordered or modified olivine structure.
[0159] The EAC can also be sulfur or Li2S.
[0160] 2) Negative electrode E n
[0161] In this case, the EAC may be selected from the group consisting of graphitic carbon capable of intercalating lithium. More details of this type of EAC can be found in Carbon 2000, 38, 1031-1041. This type of EAC is typically in the form of powder, flakes, fibers or spheres (e.g. mesophase carbon beads).
[0162] The EAC may also be: lithium metal; lithium alloy compositions (such as those described in US 6,203,944 and WO 00 / 03444); lithium titanate, generally of the formula Li4Ti5O 12 These compounds are generally considered to be “zero strain” intercalation materials that absorb mobile ions (i.e., Li + ) have a low level of physical expansion; lithium-silicon alloys with a high Li / Si ratio (commonly referred to as lithium silicide), especially those with the formula Li 4.4 Si lithium silicide, and lithium germanium alloys, including Li 4.4 Crystalline phase of Ge.
[0163] The ECM is typically selected from the group consisting of a conductive carbonaceous material and a metal powder or fiber. The conductive carbonaceous material can be selected, for example, from the group consisting of carbon black, carbon nanotubes, graphite, graphene and graphite fibers and combinations thereof. Examples of carbon black include Ketjen black and acetylene black. The metal powder or fiber includes nickel and aluminum powder or fiber.
[0164] The lithium salt (LIS) can be selected from the group consisting of: LiPF6, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, LiB(C2O4)2, LiAsF6, LiClO4, LiBF4, LiAlO4, LiNO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO3CF3)2, LiC4F9SO3, LiCF3SO3, LiAlCl4, LiSbF6, LiF, LiBr, LiCl, LiOH and 2-trifluoromethyl-4,5-dicyanoimidazole lithium.
[0165] The function of polymer binder is to keep the components of composition (C) together. Polymer binder is usually inert. Preferably, it should also be chemically stable, and contribute to electronic and ion transport. Polymer binder is well known in the art. Non-limiting examples of polymer binder include polymers (copolymers) based on vinylidene fluoride (VDF), styrene-butadiene rubber (SBR), styrene-ethylene-butylene-styrene (SEBS), carboxymethyl cellulose (CMC), polyamide-imide (PAI), poly (tetrafluoroethylene) (PTFE) and poly (acrylonitrile) (PAN) polymers (copolymers). It is preferably a fluoropolymer, more particularly a polymer (copolymer) based on VDF comprising a repeating unit derived from VDF. Polymers (copolymers) based on VDF can be, for example, polyvinylidene fluoride, or a copolymer of VDF and at least one fluorinated monomer (such as hexafluoropropylene (HFP)) different from VDF.
[0166] Based on the total weight of the composition (C), the proportion of the inorganic material M in the composition may be between 0.1 wt % and 80.0 wt %. In particular, this proportion may be between 1.0 wt % and 60.0 wt %, more particularly between 10.0 wt % and 50.0 wt %. The thickness of the electrode (E) is not particularly limited and should be adapted to the energy and power required in the application. For example, the thickness of the electrode (E) may be between 0.01 mm and 1,000 mm.
[0167] The inorganic material M can also be used to prepare a separator (SP). The separator is a permeable membrane placed between the positive electrode and the negative electrode of the battery. Its function is to allow lithium ions to pass through and block electrons, and to ensure the physical separation between the electrodes. The separator (SP) of the present invention typically comprises:
[0168] ●Inorganic material M;
[0169] ●optionally at least one polymeric binding material (P);
[0170] ●optionally at least one metal salt, especially a lithium salt;
[0171] - Optionally at least one plasticizer.
[0172] The electrode (E) and the separator (SP) can be prepared by methods well known to the skilled person. This generally involves mixing the components in a suitable solvent and then removing the solvent. For example, the electrode (E) can be prepared by a process comprising the following steps:
[0173] - applying a slurry comprising the components of composition (C) and at least one solvent to a metal substrate;
[0174] - Remove the solvent.
[0175] Common techniques known to the skilled person are as follows: coating and calendering, dry and wet extrusion, 3D printing, sintering of porous foam materials followed by impregnation. Common preparation techniques for electrodes (E) and separators (SP) are provided in Energy Environ. Sci. [Energy and Environmental Science], 2019, 12, 1818.
[0176] Examples
[0177] X-ray diffraction
[0178] The XRD patterns of the powders were obtained on an XRD goniometer in Bragg-Brentano geometry with a Cu X-ray tube (Cu Kα wavelength of ). The setup can be used in different optical configurations, i.e. with variable or fixed divergence slits, or Soller slits. It is also possible to use a filtering device on the primary side, like a monochromator or the Bragg-Brentano HD optics from Panalytical. If a variable divergence slit is used, the typical illumination area is 10mm x 10mm. The sample holder is loaded on a rotator, and the rotation speed during acquisition is typically 60rpm. With the incident Bragg-Brentano HD optics, the tube setup is operated at 40kV / 30mA for variable slit acquisition and at 45kV / 40mA for fixed slit acquisition. The acquisition step is 0.017° / step. The angular range is typically 5° to 90° of 2θ or more. The total acquisition time is typically 30min or more.
[0179] The pseudo-Voigt curve function of Thompson et al. (P. Thompson, DE Cox, JB Hastings, J. Appl. Cryst. [Journal of Applied Crystallography], 20 (1987), pp. 79-83) was used to fit the Rietveld full spectrum. The cubic LLZO phase is labeled with the I a-3d space group, and the atomic positions and occupancies are reported. In the model, the sample zero displacement, unit cell parameters, scale factors, and isotropic size and micro-constraint broadening were improved. The instrumental resolution function (IRF) was obtained from a well-crystallized LaB6 sample.
[0180] For b / a determination, the intensity was determined on the diffractogram relative to a baseline taken over the 2θ angle range between 5.0° and 90.0°. The baseline was automatically determined using the software used to analyze the diffractogram data.
[0181] Determination of d50
[0182] As mentioned above, d50 is obtained by statistical analysis of the (number) distribution of the diameter d of the primary particles, and at least one of these parameters is determined from a photograph obtained by a SEM (scanning electron microscope). The scanning electron microscope must be properly calibrated and adjusted according to the guidelines provided by the manufacturer. In addition, certified reference materials can be used to check whether the measured diameter is consistent with the actual. Determine d50 from the cumulative particle size distribution of the diameter d.
[0183] Determination of D10, D50, and D90
[0184] These parameters were obtained by laser diffraction using a Malvern Mastersizer 3000. The samples were dispersed in NMP. The raw data were analyzed using Mie theory. The following parameters were used:
[0185] - for inorganic material M: a refractive index of 2.15 and an absorption index of 0.01;
[0186] - For NMP: the refractive index is 1.46.
[0187] D US 50 and D US 90% confirmed
[0188] These parameters are obtained by laser diffraction under the same conditions as disclosed above after treatment under ultrasound. Treatment under ultrasound includes inserting an ultrasound probe into a dispersion of 100 mg of inorganic material M in 160 mL of NMP, and subjecting the dispersion to ultrasound treatment for 22 minutes at a power of 140 W ± 10 W. An external ultrasound probe (750 W generator - Synetude Lab 750) is used to adjust to deliver 140 ± 10 W. An ice bath is used to ensure that the suspension is heated to no more than 45 ° C during measurement.
[0189] An external ultrasonic probe was directly connected to the laser diffractometer, enabling determination of D50 and D90 over time (measurement every 13 seconds, 100 measurements for overall analysis of defragmentation of the particles). It was observed that for the inorganic material M of the invention, D50 and D90 decreased over time and reached a plateau.
[0190] The process of the invention enables obtaining other inorganic materials M with various compositions. See Examples 1 to 6 below.
[0191] Example 1: Inorganic materials according to the present invention M Preparation
[0192] The precursor was prepared by the method of the present invention. Solution S was prepared by mixing 387.2 g of distilled water, 95 g of La(NO3)3 solution (C=472.5 g / L, density d=1.7111), 69.8 g of ZrO(NO3)2 solution (C=268.1 g / L, d=1.415), 4.03 g of Al(NO3)3 pre-dissolved in 8 g of distilled water. Solution S was fed dropwise over 1 hour into a tank reactor (volume 1 L) stirred at 400 rpm and containing 429.5 g of distilled water and 63.4 g of concentrated ammonia (28.0 wt%). The amount of ammonia used was equivalent to an excess of 40% (molar ratio r=1.40). A white precipitate was formed.
[0193] After the addition, the mixture was discharged from the reactor and transferred into a closed pressure tank (autoclave), where it was heated at 150° C. with a heating ramp of 2.5° C. / min for 4 hours under stirring (150 rpm). The mixture was then cooled to room temperature under stirring and discharged from the autoclave.
[0194] The organic additive (lauric acid, 40 wt% based on the final expected weight of inorganic materials) was added to the precipitate under stirring (400 rpm). At the end of the addition, stirring was maintained for 30 minutes. The mixture was then filtered and washed with alkaline water (volume of alkaline water: 1 L; pH about 9).
[0195] The cake was then calcined at 500° C. for 4 hours in air. The calcination temperature of 500° C. was reached with a heating ramp of 4° C. / min. The Al-doped precursor was then ground in a mortar to obtain a homogeneous product.
[0196] In order to obtain 5 g of inorganic material M, 5.54 g of Al-doped precursor (corresponding to 90.3% oxide) was weighed. A lithium nitrate solution was prepared (3.26 g of LiNO3 was dissolved in 2.0 g of water). This corresponds to an excess of 10.0% Li. The precursor was immersed in the solution by dropping an aqueous solution of LiNO3 onto the Al-doped precursor stirred with a spatula. A wet cake was obtained at the end of this step. The cake was dried in a preheated furnace at 120°C for 2 hours and then ground in a mortar. The powder was then calcined at 900°C in air for 6 h in a covered crucible made of alumina, reaching the calcination temperature with a heating ramp of 5°C / min. The powder obtained after calcination was then ground in a mortar. The powder was then calcined for a second time in a covered crucible made of alumina at 1000°C in air for 6 hours with a heating ramp of 5C / min and a cooling ramp of 2C / min. The powder was ground in a mortar.
[0197] The relative composition of cations in the inorganic material M obtained after impregnation and calcination corresponds to Li 6.44 Al 0.22 LqCy 1.99 (determined by ICP).
[0198] Example 2: Inorganic materials according to the present invention M Preparation
[0199] Exactly the same method as described in Example 1 was carried out, except that in step (6), only one calcination step at 800° C. for 6 hours was applied. The temperature of 800° C. was reached with a heating ramp of 5° C. / min.
[0200] Example 3: Inorganic materials according to the present invention M Preparation
[0201] The same method as described in Example 1 was carried out, except that Al(NO3)3 was replaced by Ga(NO3)3 in solution S. The relative composition of the cations in the inorganic material M obtained after impregnation and calcination corresponds to Li 6.80 Al 0.05 Ga 0.19 LqCy 1.94 (determined by ICP).
[0202] Example 4: Inorganic materials according to the present invention M Preparation
[0203] The same method as described in Example 1 was carried out, except that a mixture of Al(NO3)3 and Ga(NO3)3 was used in solution S. The relative composition of the cations in the inorganic material M obtained after impregnation and calcination corresponds to Li 6.65 Al 0.13 Ga 0.10 LqCy 1.94 (determined by ICP).
[0204] Example 5: Inorganic materials according to the present invention M Preparation
[0205] The precursor was prepared by the method of the present invention. Solution S was prepared by mixing 393.4 g of distilled water, 95.66 g of La(NO3)3 (C=472.5 g / L, density d=1.7111), 52.78 g of ZrO(NO3)2 (C=268.1 g / L, d=1.415), 18.73 g of a precipitate having the formula C6H4NNbO 12 The solution S was fed dropwise over 1 hour into a tank reactor (volume 1 L) stirred at 400 rpm and containing 428.4 g of distilled water and 64.4 g of concentrated ammonia (28.0 wt%). The amount of ammonia used corresponded to an excess of 40% (molar ratio r=1.40). A white precipitate was formed.
[0206] After the addition, the mixture was heated in a reactor at 98° C. for 4 hours with stirring (400 rpm). The mixture was then allowed to cool to room temperature overnight with stirring.
[0207] An organic additive (lauric acid, 40% of the expected final oxide weight) was added to the precipitate under stirring (400 rpm). At the end of the addition, stirring was continued for 30 minutes. The mixture was then filtered and washed with alkaline water (volume of alkaline water: 1 L; pH about 9).
[0208] The cake was then calcined at 500° C. for 4 hours in air. The calcination temperature of 500° C. was reached with a heating ramp of 4° C. / min. The Nb-doped precursor was then ground in a mortar to obtain a homogeneous product.
[0209] In order to obtain 5 g of inorganic material M, 5.58 g of Nb-doped precursor (corresponding to 89.7% oxide) was weighed. A lithium nitrate solution was prepared (3.06 g of LiNO3 was dissolved in 2.9 g of water). This corresponds to an excess of 10.0% Li. The precursor was immersed in the solution by dropping an aqueous solution of LiNO3 onto the Nb-doped precursor stirred with a spatula. A wet cake was obtained at the end of this step. The cake was dried at 110°C in a preheated furnace for 2 hours and then ground in a mortar. The powder was then calcined at 900°C in air for 6 h in a covered crucible made of alumina, reaching the calcination temperature with a heating ramp of 5°C / min. The powder was then ground in a mortar. The powder was then calcined for a second time in a covered crucible made of alumina in air at 1000°C with a heating ramp of 5C / min and a cooling ramp of 2C / min for 6 hours. The powder was ground in a mortar. The relative composition of cations in the inorganic material M obtained after impregnation and calcination corresponds to Li 7.00 Al 0.03 Nb 0.57 LqCy 1.45 (determined by ICP).
[0210] Example 6: Inorganic materials according to the present invention M Preparation
[0211] The precursor was prepared by the method of the present invention. Solution S was prepared by mixing 395 g of distilled water, 94.24 g of La(NO3)3 (C=472.5 g / L, density d=1.7111), 69.26 g of ZrO(NO3)2 (C=268.1 g / L, d=1.415), 4.39 g of Fe(NO3)3. Solution S was fed dropwise over 1 hour into a tank reactor (volume 1 L) stirred at 400 rpm and containing 433.8 g of distilled water and 66.2 g of concentrated ammonia (28.0 wt%). The amount of ammonia used was equivalent to an excess of 40% (molar ratio r=1.40). A white precipitate was formed.
[0212] After the addition, the mixture was discharged from the reactor and transferred into a closed pressure tank (autoclave), where the mixture was heated at 150° C. with a heating ramp of 2.5° C. / min for 4 hours under stirring (150 rpm). The mixture was then cooled to room temperature under stirring and discharged from the autoclave.
[0213] An organic additive (lauric acid, 40% of the expected final oxide weight) was added to the precipitate under stirring (400 rpm). At the end of the addition, stirring was continued for 30 minutes. The mixture was then filtered and washed with alkaline water (volume of alkaline water: 1 L; pH about 9).
[0214] The cake was then calcined at 500° C. for 4 hours in air. The calcination temperature of 500° C. was reached with a heating ramp of 4° C. / min. The Fe-doped precursor was then ground in a mortar to obtain a homogeneous product.
[0215] In order to obtain 5 g of inorganic material M, 5.62 g of Fe-doped precursor (corresponding to 89.0% oxide) was weighed. A lithium nitrate solution was prepared (2.96 g of LiN was dissolved in 4.4 g of water). This corresponds to an excess of 10.0% Li. The precursor was immersed in the solution by dropping an aqueous solution of LiN onto the Fe-doped precursor stirred with a spatula. A wet cake was obtained at the end of this step. The cake was dried in a preheated furnace at 120°C for 2 hours and then ground in a mortar. The powder was then calcined at 900°C in air for 6 h in a covered crucible made of alumina, reaching the calcination temperature with a heating ramp of 5°C / min. The powder was then ground in a mortar. The powder was then calcined for a second time in a covered crucible made of alumina in air at 1000°C with a heating ramp of 5C / min and a cooling ramp of 2C / min for 6 hours. The powder was ground in a mortar.
[0216] The relative composition of cations in the inorganic material M obtained after impregnation and calcination corresponds to Li 6.91 Al 0.05 Fe 0.21 LqCy 1.97 (determined by ICP).
[0217] Comparative Example C1: Preparation of Inorganic Materials by Conventional Solid-State Techniques
[0218] Inorganic materials are prepared by conventional solid state techniques. To this end, 10.44 g Li CO , 9.80 g ZrO , 19.40 g La O and 0.41 g Al O were mixed together using a 3D oscillator with a ball (diameter = 1 cm) made of ZrO -Y O during 2 h. The powder / ball / air ratio was 1 / 3 / 1 / 3 / 1 / 3 (by volume). 19.5 g of the resulting mixture was added to an alumina crucible with an alumina lid and calcined in air at 900 ° C with a heating ramp of 5 C / min and a cooling ramp of 2 C / min during 12 h. The calcined powders were mixed in a 3D oscillator using the same ball in the same ratio for 2 h, as disclosed. The mixture was then calcined in air at 1000 ° C with a heating ramp of 5 C / min and a cooling ramp of 2 C / min for 12 h, followed by mixing again in a 3D oscillator with the same ball for 2 h. Finally, a final calcination step at 1100°C with a heating ramp of 5 C / min and a cooling ramp of 2 C / min for 12 h was performed followed by grinding to obtain the final product.
[0219] Comparative Example C2: Preparation of Inorganic Materials without Lauric Acid
[0220] The formulation used corresponded to the formulation described in Example 1, except that it did not contain any lauric acid.
[0221] Table I
[0222]
Claims
1. An inorganic material M, comprising or consisting of a garnet oxide or a garnet-type oxide containing the elements Li, La, Zr and at least one element A selected from the group consisting of Al, Ga, Nb, Fe, W, Ta or a mixture thereof as constituent elements, wherein the oxide is described by formula (I): [Li x1 La3Zr z A w O 12 ](I) in: ■x1, z and w are positive real numbers; ■1.20<z≤2.10; ■0<w≤0.80; ■x1 is derived from the electrical neutrality of the oxide; The inorganic material exhibits: ■Ratio R50 higher than 50%, R50 is defined as follows: R50(%)=(D50-D US 50) / D50 x 100 Among them, D50 and D US 50 is the volume distribution median diameter of the diameter of the dispersion of the particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameter is obtained by laser diffractometer, D US 50 is measured after ultrasonic treatment, the ultrasonic treatment comprising inserting an ultrasonic probe into a dispersion of 100 mg of the inorganic material M in 160 mL of NMP, and subjecting the dispersion to ultrasonic treatment at a power of 140±10 W for 22 minutes; and / or ■Ratio R90 higher than 50%, R90 is defined as follows: R90(%)=(D90-D US 90) / D90 x 100 Among them, D90 and D US D90 corresponds to the diameter of the particles in which 90% of the particles have a diameter less than D90 and is determined from the volume distribution of the diameters of a dispersion of these particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameters being obtained with a laser diffractometer, D US 90 is measured after treatment under ultrasound, which includes inserting an ultrasound probe into a dispersion of 100 mg of the inorganic material M in 160 mL of NMP and subjecting the dispersion to ultrasound treatment at a power of 140±10 W for 22 minutes.
2. An inorganic material M, comprising or consisting of a garnet oxide or a garnet-type oxide containing the elements Li, La, Zr and at least one element A selected from the group consisting of Al, Ga, Nb, Fe, W, Ta or a mixture thereof as constituent elements, wherein the oxide is described by formula (I): [Li x1 La3Zr z A w O 12 ](I) in: ■x1, z and w are positive real numbers; ■1.20<z≤2.10; ■0<w≤0.80; ■x1 is derived from the electrical neutrality of the oxide; The inorganic material exhibits: ■Ratio R50 higher than 50%, R50 is defined as follows: R50(%)=(D50-D US 50) / D50 x 100 Among them, D50 and D US 50 is the volume distribution median diameter of the diameter of the dispersion of the particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameter is obtained by laser diffractometer, D US 50 was measured after treatment under ultrasound, which included inserting an ultrasound probe into a dispersion of 100 mg of the inorganic material M in 160 mL of NMP and subjecting the dispersion to ultrasound treatment at a power of 140±10 W for 22 minutes.
3. The inorganic material M according to claim 1 or claim 2, in: 1.40≤z≤2.05。 4. The inorganic material M according to claim 1 or claim 2, wherein: 1.20≤z≤2.05; 0<w≤0.60; The inorganic material exhibits: Ratio R50 above 60%; and / or Ratio R90 higher than 60%.
5. The inorganic material M according to claim 1 or claim 2, wherein: 1.50≤z≤2.00; 0<w≤0.30; The inorganic material exhibits: Ratio R50 above 70%; and / or Ratio R90 higher than 70%.
6. The inorganic material M according to claim 1 or claim 2, wherein: 0<w≤0.25; The inorganic material exhibits: Ratio R50 above 80%; and / or Ratio R90 higher than 80%.
7. The inorganic material M according to claim 1 or claim 2, wherein: The relative composition of the cations in the inorganic material M corresponds to the following formula: <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> La3Zr<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> (II) in: ■w, x and z are positive real numbers; ■1.20<z≤2.10; ■0<w≤0.80; ■4.00≤x≤10.5。 8. The inorganic material M according to claim 7, wherein: 1.40≤z≤2.05; 0<w≤0.60; 5.10≤x≤9.1。 9. The inorganic material M according to claim 7, wherein: 1.50≤z≤2.00; 0<w≤0.30; 6.20≤x≤7.7。 10. The inorganic material M according to claim 7, wherein: 0<w≤0.25。 11. The inorganic material M according to claim 1 or claim 2, wherein: The relative composition of the cations in the inorganic material M corresponds to the following formula: <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> La3Zr<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> A1<h2 style=";text-align:left;direction:ltr"> w1 <h2 style=";text-align:left;direction:ltr"> A2<h2 style=";text-align:left;direction:ltr"> w2 <h2 style=";text-align:left;direction:ltr"> (IIa) in: ■A1 is selected from the group consisting of Al, Ga, Fe or a combination thereof; ■A2 is selected from the group consisting of Nb, Ta or a combination thereof; ■w1, w2, x and z are positive real numbers; ■1.20<z≤2.10; ■0<w1≤0.20; ■0.10<w2≤0.80; ■ w1 and w2 are such that w = w1 + w2 and w ≤ 0.80; ■5.60≤x≤10.35。 12. The inorganic material M according to claim 11, wherein: 1.20<z≤2.05; 0.20<w2≤0.80; 5.60≤x≤8.84。 13. The inorganic material M according to claim 11, wherein: 1.50≤z≤2.00; 0.20<w2≤0.50; 5.90≤x≤7.48。 14. The inorganic material M according to claim 1 or claim 2, wherein: The relative composition of the cations in the inorganic material M corresponds to the following formula: <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> La3Zr<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> A1<h2 style=";text-align:left;direction:ltr"> w1 <h2 style=";text-align:left;direction:ltr"> A2<h2 style=";text-align:left;direction:ltr"> w2 <h2 style=";text-align:left;direction:ltr"> (IIb) in: ■A1 is selected from the group consisting of Al, Ga, Fe or a combination thereof; ■A2 is W; ■w1, w2, x and z are positive real numbers; ■1.20<z≤2.10; ■0<w1≤0.20; ■0.10<w2≤0.80; ■ w1 and w2 are such that w = w1 + w2 and w ≤ 0.80; ■4.80≤x≤10.20。 15. The inorganic material M according to claim 14, wherein: 1.20<z≤2.05; 0.20<w2≤0.80; 4.80≤x≤8.58。 16. The inorganic material M according to claim 14, wherein: 1.50≤z≤2.00; 0.20<w2≤0.50; 5.40≤x≤7.26。 17. The inorganic material M according to claim 1 or claim 2, wherein: 1.90≤z≤2.10。 18. The inorganic material M according to claim 1 or claim 2, wherein: w≥0.05。 19. The inorganic material M according to claim 1 or claim 2, wherein: The inorganic material M and / or the oxide exhibits a cubic structure.
20. The inorganic material M according to claim 19, wherein The cubic structure is described by either the Ia-3d space group or the I-43d space group.
21. The inorganic material M according to claim 1 or claim 2, wherein: The crystal structure of this oxide consists of a framework of eight-fold coordinated LaO8 dodecahedrons and six-fold coordinated ZrO6 octahedrons.
22. The inorganic material M according to claim 1 or claim 2, wherein: The crystal structure of this oxide includes LiO4 tetrahedrons and LiO6 octahedrons.
23. The inorganic material M according to claim 21, wherein The inorganic material M contains lithium cations outside the crystal structure.
24. The inorganic material M according to claim 22, wherein The inorganic material M contains lithium cations outside the crystal structure.
25. The inorganic material M according to claim 1 or claim 2, wherein: In this oxide, Zr is partially replaced by Hf.
26. The inorganic material M according to claim 25, wherein The molar ratio Hf / Zr is between 1 / 100 and 5 / 100.
27. The inorganic material M according to claim 25, wherein The molar ratio Hf / Zr is between 1 / 100 and 2 / 100.
28. The inorganic material M according to claim 1 or claim 2, wherein: The primary particles of the inorganic material M exhibit a d50 between 0.5 μm and 7.0 μm.
29. The inorganic material M according to claim 1 or claim 2, wherein: The primary particles of the inorganic material M exhibit a d50 between 0.5 μm and 5.0 μm.
30. The inorganic material M according to claim 1 or claim 2, wherein: The primary particles of the inorganic material M exhibit a d50 between 0.5 μm and 3.0 μm.
31. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D50 between 10.0 and 50.0 μm.
32. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D50 between 10.0 and 40.0 μm.
33. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D50 between 10.0 and 35.0 μm.
34. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D90 of less than 150.0 μm.
35. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D90 between 20.0 and 150.0 μm.
36. The inorganic material M according to claim 1 or claim 2, wherein: The particles of the inorganic material M exhibit a D90 between 20.0 and 100.0 μm.
37. The inorganic material M according to claim 1 or claim 2, wherein: These particles of the inorganic material M exhibit a D10 greater than and equal to 0.5 μm, D10 corresponding to the diameter of the particles where 10% of the particles have a diameter less than D10, and is determined by the volume distribution of the diameters of a dispersion of these particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameters being obtained using a laser diffractometer.
38. The inorganic material M according to claim 1 or claim 2, wherein: These particles of the inorganic material M exhibit a D10 between 0.5 and 15.0 μm, D10 corresponding to the diameter of the particles where 10% of the particles have a diameter less than D10, and is determined by the volume distribution of the diameters of a dispersion of these particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameters being obtained using a laser diffractometer.
39. The inorganic material M according to claim 1 or claim 2, wherein: These particles of the inorganic material M exhibit a D10 between 0.5 and 10.0 μm, D10 corresponding to the diameter of the particles where 10% of the particles have a diameter less than D10, and is determined by the volume distribution of the diameters of a dispersion of these particles of the inorganic material M in N-methyl-2-pyrrolidone (NMP), the volume distribution of the diameters being obtained using a laser diffractometer.
40. The inorganic material M according to claim 1 or claim 2, which exhibits an intensity ratio b / a of less than 0.05, a and b being the intensities of peaks visible at 2θ between 16.0° and 17.0° and at 2θ between 28.5° and 28.7°, respectively, on the XRD pattern.
41. A method for preparing the inorganic material M according to any one of claims 1 to 40, the method comprising the following steps: (1) contacting an aqueous solution S comprising (i) a zirconium salt, (ii) a lanthanum salt and (iii) a salt of the element A or a precursor of an oxide of the element A with an aqueous solution of a basic compound, resulting in a precipitate suspended in a reaction medium; (2) stirring the reaction medium obtained at the end of step (1) for at least 30 minutes; (3) contacting the precipitate obtained at the end of step (2) with an additive selected from the group consisting of anionic surfactants, nonionic surfactants, polyethylene glycol, carboxylic acids and their salts, and a surfactant of the carboxymethylated fatty alcohol ethoxylate type; (4) calcining the precipitate recovered at the end of the previous step in air at a temperature of at least 400° C.; (5) contacting the product obtained at the end of step (4) with a lithium salt; (6) calcining the product obtained at the end of step (5) in air at a temperature between 700° C. and 1100° C.; The inorganic material M comprises garnet oxide or garnet-type oxide containing the elements Li, La, Zr and at least one element A selected from the group consisting of Al, Ga, Nb, Fe, W, Ta or a mixture thereof as constituent elements, or consists of the garnet oxide or garnet-type oxide.
42. The method according to claim 41, wherein: The zirconium salt is selected from the group consisting of zirconium nitrate and zirconium chloride.
43. The method according to claim 41 or 42, wherein: In step (2), the reaction medium is stirred for at least 30 minutes, and the temperature of the reaction medium is between 50°C and 200°C.
44. The method according to claim 41 or 42, wherein: In step (2), the reaction medium is stirred for at least 30 minutes, and the temperature of the reaction medium is between 80°C and 150°C.
45. The method according to claim 41 or 42, wherein: The additive is a carboxylic acid or a salt thereof.
46. The method of claim 41 or 42, wherein: The additive is lauric acid or ammonium laurate.
47. The method according to claim 41 or 42, wherein: The calcination temperature in step (4) is between 400°C and 800°C.
48. The method according to claim 41 or 42, wherein: The calcination temperature in step (4) is between 400°C and 600°C.
49. The method according to claim 41 or 42, wherein: The contacting of step (5) comprises impregnating the product obtained at the end of step (4) with an aqueous solution of a lithium salt, or mixing the product obtained at the end of step (4) and the lithium salt together, both of which are in powder form.
50. The method of claim 41 or 42, wherein: In step (6), the product obtained at the end of step (5) is calcined firstly in air at a temperature between 700° C. and 900° C. and then in air at a temperature between 900° C. and 1100° C.
51. An inorganic material M obtainable by a method according to any one of claims 41 to 50.
52. A composition (C) comprising: (i) an inorganic material M as described in any one of claims 1 to 40 or claim 51; (ii) at least one electroactive compound (EAC); (iii) optionally at least one lithium ion conducting material (LiCM) other than the inorganic material M; (iv) optionally at least one electrically conductive material (ECM); (v) optionally a lithium salt (LIS); (vi) optionally at least one polymeric binding material (P).
53. An electrode (E), comprising: ●Metal substrate; At least one layer L made of a composition (C) as claimed in claim 52, adhered directly to the metal substrate.
54. A membrane (SP), comprising: ● an inorganic material M as claimed in any one of claims 1 to 40 or claim 51; ●optionally at least one polymeric binding material (P); ●optionally at least one metal salt; - Optionally at least one plasticizer.
55. Separator (SP) as claimed in claim 54, wherein said at least one metal salt is a lithium salt.
56. Use of the inorganic material M according to any one of claims 1 to 40 for preparing a lithium ion battery.
57. A lithium ion battery comprising the inorganic material M according to any one of claims 1 to 40.
Citation Information
Patent Citations
Method for producing garnet-type lithium ion-conducting oxide and garnet-type lithium ion-conducting oxide
JP2012224520A
Method for producing garnet type lithium ion-conductive oxide
JP2013256435A
Garnet-type lithium-lanthanum-zirconium composite oxide and method for producing the same
JP2018065704A
Garnet-Type Oxide Sintered Body and Method for Producing Same
US20180175446A1
Method for preparing solid electrolyte for all-solid-state lithium secondary battery
US20180248223A1